The Analysis of Fractional-Order Proportional Delay Physical Models via a Novel Transform. (15th February 2022) - Alesemi, Meshari; Iqbal, Naveed; Hamoud, Ahmed A.
Abstract : In this paper, we deal with an alternative analytical analysis of fractional-order partial differential equations with proportional delay, achieved by applying Yang decomposition method, where the fractional derivative is taken in Caputo sense. The suggested series results are discovered to quickly converge to an exact solution. The computation of three test problems of fractional-order with proportional delay partial differential equations was presented to confirm the validity and efficiency of suggested method. The system appears to be a very dependable, effective, and powerful method for solving a variety of physical problems that arise in engineering and science.